Pengaruh Motif Penggunaan Media Tiktok Terhadap Citra Diri Pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam - Batin, Mail Hilian; Riski, Oki Sania; Asmy, Sinsin; Hidayat, Fajri Nur (Forum Kerjasama Pendidikan Tinggi, 2023)
The social media presence of TikTok is currently mushrooming. This is coupled with the presence of several innovations that make users spoiled for long using the application. The platform user market segment targets millennial children or young people, so that user creativity is required to be able to present interesting content. There are users who only use this platform as active and passive users. There are several motives behind all of this, therefore researchers conduct research related to testing the influence of motives for using the TikTok application on self-image in students. This type of research is quantitative by distributing questionnaires in the form of a Google form link. The students who were sampled were from class 2019 to 2022. The total study population was 2,858 active students, while the sample consisted of 338 students based on the krecjre table with a 95% confidence level or 5% error and N = 2800. Data analysis techniques are respondent profiles, validity and reliability tests, classic assumption tests, and hypothesis testing. From the tests that have been carried out, that there is an influence between the motive variable for using TikTok on Student Self-Image, and the self-motivated variable has a coefficient of determination of 50.9% while the rest is influenced by other variables.